Edwin Markham papers - Markham, Edwin, 1852-1940.
Correspondence, autobiographical notes, drafts and published versions of poems, notebooks of writings on poems and religion, and printed matter. Includes an annotated typescript with a cover note by H. L. Mencken and page proofs from the American Mercury of Markham's poem, The Ballad of the Gallows-bird. Correspondents include Amelia Josephine Burr, Frederic Lathrop Colver, William Griffith, Robert Underwood Johnson, Anna Catherine Markham, and George Sylvester Viereck.
Poet and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burr, Amelia Josephine, -- 1878- -- Correspondence; Colver, Frederic Lathrop, -- 1863- -- Correspondence; Griffith, William, -- 1876-1936 -- Correspondence; Johnson, Robert Underwood, -- 1853-1937 -- Correspondence; Markham, Anna Catherine, -- 1859-1938 -- Correspondence; Mencken, H. L. -- 1880-1956.; Viereck, George Sylvester, -- 1884-1962 -- Correspondence; American mercury (New York, N.Y. : 1924); American poetry; Religion; Educators; Poets